Exploring the life experiences of school‐aged children afflicted by tethered spinal cord syndrome: An interpretative qualitative study - Nan Lin; Mingxian Ren; Yujun Xiang; Jiahuan Li; Dan Wang; Hongzhen Xu (Health Expectations)
Abstract Background Children affected by tethered cord syndrome (TCS) encounter multifaceted challenges encompassing educational, familial and social spheres, underscoring the significance of a holistic comprehension of their subjective emotional well‐being and life encounters. Nonetheless, healthcare professionals tend to prioritise the physical functionality of the afflicted individuals throughout the treatment and rehabilitation process, often neglecting the emotional experiences and requirements of these children as they transition into posthospitalization phases. Aim To advance the subjective experiences and perceptions of children with TCS upon reintegration into their families, educational institutions and wider societal contexts subsequent to their discharge from medical facilities. Methods The study was conducted at the Children's Hospital in Zhejiang. Twelve children aged 8–15 with TCS were included in the study. The research design used an interpretative qualitative approach, utilising semi‐structured interviews as the primary data collection method. Data analysis was performed using reflexive thematic analysis, facilitating a comprehensive exploration of emerging themes and patterns. Results Four major themes (and seven subthemes) were identified from the findings: (1) growing pains (a shameful secret, distance between ideal and reality); (2) inappropriate expressions of familial affection (knowing is not understanding, unspeakable guilt); (3) social estrangement (uncomfortable distinctions, familiar stranger) and (4) striving for independence and consistency. Conclusions Children affected by TCS exhibit internal sensitivity and challenges in self‐development, family dynamics and social interactions. They aspire to attain a future characterised by independence and freedom, akin to that of their typically developing peers. These findings can help health professionals, families and educators gain a deeper understanding of what it takes to be a child with TCS, and the findings can also serve as a platform for interventions that seek to promote self‐expression in these children so that they can experience life as a meaningful and positive process. Patient or Public Contribution This study received support from children with TCS and their guardians during data collection, as well as from the head nurse of the unit. Coresearchers also contributed to design, data collection, analysis and writing.